The performance of Malaysian Industrial Development Finance (MIDF): analysis based on profitability / Siti Hajar Mohd Asri - Mohd Asri, Siti Hajar (2011)
Profitability is the major elements that determine the robust establishment of one company in the industry. The profitability performance is depends on company ability to generate more revenue than spending on their expenses. The objectives of this research paper are to analyze the profitability performance of Malaysian Industrial Development Finance (MIDF) from year 2005 to 2009. MIDF is the financial institution that offers several financial products especially in SME industry and also serve as investment banking entity for the sole purpose of servicing corporate clients. Then, the researcher will identify the gap between profitability management theories and the company accounting practices. The gaps identified later are used as a guideline to come out with a few suggestions on how to increase the company profitability. The profitability performance will be measure using profitability ratio which are Gross Profit Margin, Net Profit Margin, Return on Assets and Return on Equities. The data of this study is collected from company annual report, company internal magazines, internal policies and procedures, face to face interview, trainings, company official website, journals and text books. Findings show that the company profitability performance is at average level. The reducing in company revenue had affected the profitability of the company. However, the action taken to minimize the operating expenses is successful in maintaining the company profit.